Pratiques culturales et mortalités d'huîtres creuses Crassostrea gigas en baie de Quiberon, en 2001-2002. Bilan des enquêtes, plongées et prélèvements sur 18 semis en 2001-2002 - Mazurie, Joseph; Langlade, Aime; Fleury, Pierre-gildas; Bouget, Jean-francois; Claude, Serge; Foucart, Marie; Bedier, Edouard (2003)
This study is the second part of a former report rapport Ifremer DRV/RST/RA/LCB/2002-08 dealing with rearing methods, growth and mortality performances, and problems encountered by the oyster farmers from Quiberon Bay (2800 ha of leases) : the first report relied on a survey achieved in july 200l, about 18 oyster farmers, and 2 diving campaigns (july and october 2001) on 2 years old oyster batches from the same farmers. Il is now completed by a last campaign of diving in october 2002, on 7 parcels out of the 18, still bearing the initial oysters. The analysed enterprises vary in particular by the location and depth of their concession inside the bay, but also by their rearing scheme : a majority favours seedings with 18 month old oysters or more, according to prices and availability of oysters supplies. This part of the study provides in particular a tool of profitability simulation, based on technical (growth, survival) and economical (prices of different oysters categories) hypothesis. Theses references may be used in ecosystem studies or long run monitoring of the area. L'étude fait suite à un premier rapport Ifremer DRV/RST/RA/LCB/2002-08 sur les méthodes d'élevage, les performances de croissance-mortalité et les problèmes rencontrés par les éleveurs d'huîtres creuses de la baie de Quiberon (2800 ha concédés), qui s'appuyait sur une enquête réalisée en juillet 2001 auprès de 18 exploitants, et 2 campagnes de plongée (juillet et octobre 2001) sur des semis d'huîtres de 2 ans des mêmes concessionnaires. Le complément est fourni par une dernière campagne de plongée en octobre 2002, sur les 7 semis parmi les 18 encore en place à cette date. Les entreprises étudiées se différencient par leur outil de production et en particulier l'emplacement de la concession en baie de Quiberon, mais également part le schéma d'élevage : une majorité privilégie les semis d'huîtres de 18 mois ou plus, en adaptant leurs approvisionnements aux disponibilités et prix du moment, mais certains sèment préférentiellement du naissain ou ...